Tanggung Jawab Notaris Sebagai Pihak Akomodir Dalam Perjanjian Kredit Perbankan - Satya Wicaksana Sudrajat; Paramita Prananingtyas (Magister Kenotariatan Universitas Diponegoro, 2023)
AbstractNotary's responsibility for c using standard clauses is associated with the principle of freedom of contract is if it contains elements of unlawful acts in a deed of credit agreement then the notary must be civilly responsible by making compensation to the injured parties based on the provisions of Article 84 of Law Number 30 of 2004 juncto Law Number 2 of 2014 concerning Notary Positions. This research uses normative juridical approach method supported empirical juridical. Based on the results of the research it is known that the application of standard agreements in credit agreements made by Notary is the main format of bank credit agreements, which in the next development towards format is still possible negotiations which means a reflection on the principle of freedom of contract. Notary public must be careful in the implementation of the making of credit agreement deed authentically, because if notary public commits mistakes or omissions in the procedure of making it, then the Notary must be responsible for the losses suffered by the parties for the degradation of the authentic deed of credit agreement at the bank into a deed under the hands, which will harm the notary public.Keywords: responsibility; notary public; credit agreementAbstrakTanggung Jawab notaris terhadap perjanjian kredit menggunakan klausula baku dikaitkan dengan asas kebebasan berkontrak adalah jika mengandung unsur perbuatan melawan hukum dalam suatu akta perjanjian kreditnya maka notaris wajib bertanggung jawab secara perdata yakni dengan melakukan ganti rugi kepada para pihak yang dirugikan berdasarkan ketentuan Pasal 84 Undang-Undang Nomor 30 Tahun 2004 juncto Undang-Undang Nomor 2 Tahun 2014 Tentang Jabatan”Notaris. Penelitian ini menggunakan metode pendekatan yuridis normatif di dukung yuridis empiris. Berdasarkan“hasil penelitian diketahui bahwa penerapan perjanjian baku dalam perjanjian kredit yang dibuat oleh Notaris merupakan format pokok dari perjanjian kredit bank, yang”dalam perkembangan selanjutnya tehadap format ini masih dimungkinkan adanya negosiasi yang berarti cerminan atas asas kebebasan berkontrak. Notaris harus berhati-hati dalam pelaksanaan pembuatan akta perjanjian kredit secara otentik, karena apabila Notaris melakukan kesalahan/kelalaian dalam prosedur pembuatannya, maka Notaris wajib bertanggungjawab atas kerugian yang diderita oleh para pihak atas terdegradasinya akta autentik perjanjian kredit pada bank tersebut menjadi akta di bawah tangan, yang akan merugikan notaris.Kata kunci: tanggung jawab; notaris; perjanjian kredit